The Arts of Citizenship in African Cities
XII, 310 p. 8 illus.
Keywords: The Arts of Citizenship in African Cities pushes the frontiers of how we understand cities and citizenship and offers new perspectives on African urbanism. Nuanced ethnographic analyses of life in an array of African cities illuminate the emergent infrastructures and spaces of belonging through which urban lives and politics are being forged.